challenges and possibilities of memory and reconciliation: empirical evidence for Colombia (2022)
The signing of the peace agreement with the Revolutionary Armed Forces of Colombia-People’s Army (FARC-EP) deepened the debate on the reconstruction of memory as a right of the victims and a way to advance in the reconciliation of Colombian society. This article uses data from the 2019 Colombian Reconciliation Barometer of the Program of Alliances for Reconciliation of the United States Agency for International Development and ACDI/VOCA to analyze the individual and contextual factors that affect how individuals perceive the reconstruction of memory as a tool that contributes to reconciliation. We estimated a probabilistic model for which the dependent variable is the predisposition toward memory reconstruction as a predictor of reconciliation based on the context of the Colombian armed conflict, and a set of individual factors that capture the effects of community initiatives and state institutions and programs arising within the framework of transitional justice. We sought to verify whether the characteristics of individuals and their way of relating to each other in a community and municipal context shape the perception of the contribution of reconstructed memory to reconcil iation. The results show that being a female victim of the armed conflict, developing empathy, residing in municipalities with the presence of Places of Memory, and trusting in the processes of transitional justice —such as clarifying the truth— increase an individual’s predisposition to consider that the reconstruction of memory contributes to reconciliation. In contrast, other policies and programs that emerged after the agreement, such as residing in municipalities with Territorially Focused Development Plans (PDET in Spanish) and the presence of Casas de Verdad (Truth Houses), operate in the opposite direction. This work suggests challenges for transitional justice by identifying the factors that condition positive outlooks toward the reconstruction of memory in reconciliation processes and opens the possibility of formulating actions with greater citizen acceptance.